PMO-038 A re-audit to evaluate the use of the spinal nutrition screening tool in the national spinal injuries centre (NSIC) at stoke Mandeville hospital. (28th May 2012) - Wong, S S H; Spillman, L; Doraikannu, J; Graham, A; Green, D; Grimble, G; Forbes, A
Abstract : Introduction: Malnutrition is common in patients with spinal cord injuries (SCI). 1 National guidelines 2 3 have set recommended standards for nutrition screening in patients with SCI. An unpublished audit to assess the use of the Spinal Nutrition Screening Tool (SNST) found that in 2009 the use was low. Methods: The present audit aimed to reassess the use of SNST and whether there had been any improvement since 2009. Ninety-three adults (mean age: 51.4 years, SD: 17.3, 17.2% female) with SCI (53.7% tetraplegia; 51.6% complete SCI) were audited in December 2011, on five in-patient wards. Data from individual patient notes were collected by two trained professionals (dietitian and nurse) using a standardised questionnaire. Results: Seventy-one (76.3%) sets of notes had a SNST form. Sixty-nine (74.2%) patients had their weight measured on admission, 49 (52.6%) had their height recorded, and 59 (63.4%) had their SNST fully completed. At the time of audit, 47.9% of patients were found to be at risk of undernutrition, 11.5% had a body mass index <20 kg/m 2, and 19.4% were found to have eaten less than half of their last meal. The current audit showed that the use of the SNST has improved significantly: 2009 vs 2011: ward A: 0% vs 73.3%, p<0.01; ward p: 0% vs 33.3%, p=0.01; ward G: 23.5% vs 77.3%, p<0.01; Ward D: 22% vs 52%, p=0.03; ward J: 47.6% vs 81.3%, p=0.01;] and in the NSIC overall: 24% vs 63.4%, [p<0.001]. Conclusion: The uptake of nutrition screening appears to have improved in the NSIC but with much still to be achieved. A nutrition steering group has been set up to monitor and evaluate the implementation of nutrition policy on a continuing basis. Competing interests: S Wong: None declared, L Spillman: None declared, J Doraikannu: None declared, A Graham: None declared, D Green: None declared, G Grimble: None declared, A Forbes grant/research support from: National Institute for Health and Research. References: 1. Wong S, et al. Eur J Clin Nutr 2011 . doi:10.1038/ejcn.2011.209 2. NICE . Nutrition Support in Adults: Oral Nutrition Support, Enteral Tube Feeding And Parenteral Nutrition. NICE, 2006. 3. Royal College of Physicians. Chronic Spinal Cord Injury: Management of Patients in Acute Hospital Settings: National Guidelines . London: Royal College of Physicians, 2008.